Poziotinib for EGFR and HER2 exon 20 insertion mutation in advanced NSCLC: Results from the expanded access program. (May 2021) - Prelaj, Arsela; Bottiglieri, Achille; Proto, Claudia; Lo Russo, Giuseppe; Signorelli, Diego; Ferrara, Roberto; Galli, Giulia; De Toma, Alessandro; Viscardi, Giuseppe; Brambilla, Marta; Lobefaro, Riccardo; Nichetti, Federico; et al.
Abstract: Background: The treatment of metastatic non–small-cell lung cancer (mNSCLC) patients with EGFR/HER2 exon 20 insertion mutation (i-mut) remains an unmet clinical need. Poziotinib, a new generation tyrosine kinase inhibitor, is currently under investigation as a potential targeted therapy. This compassionate study of its use aims to describe the activity/toxicity of poziotinib in mNSCLC with EGFR/HER2-exon-20-i-mut. Patients and methods: NSCLC patients who were treated either with EGFR or HER2 exon 20-i-mut within an expanded access program were included in this study. Poziotinib (16 mg or less) was administrated orally quaque die (QD). The primary end-point was the overall response rate (ORR) assessed by central review using RECIST v1.1, and secondary end-points were median progression free survival (PFS), disease control rate (DCR), median overall survival (OS) and toxicity. Results: The median age of all the 30 patients was 58 years (25–80 years), most of them were females (73%); ECOG 0–1 (83%), EGFR i-mut (73%) and pre-treated (83%). 73% started with poziotinib at a dose of 16 mg. At data cut-off, 22 of 33 patients (73%) experienced a progress in the disease and 12 of 30 (40%) died. Median PFS was 5.6 months (95% CI: 3.6–6.7 months) and the mOS 9.5 months (95% CI: 5.3 – not-reached months). The ORR was 30% (EGFR/HER2: 23/50%) and DCR 80%. G3 AEs were reported in 66% of the patients and were found with skin rash (50%), diarrhoea (17.6%), mucositis (7%) and paronychia (3%). G5, possibly associated with pneumonitis might also have occurred. Conclusions: Poziotinib exhibited effects in mNSCLC patients with EGFR/HER2-exon 20-i-mut. The toxicity rate was high leading to frequent dose interruption and reduction, thereby reducing mPFS in patients with good ORR/DCR. ZENITH20 trial is now being used to evaluate the low dose and new scheduled dose (e.g. bis in die (BID)). Highlights: Treatment of NSCLC patients with EGFR and HER2 exon 20 insertion mutation remains an unmet clinical need. Poziotinib is currently under investigation as a potential targeted therapy. Poziotinib demonstrated clinical activity in NSCLC. Poziotinib rate was high leading to frequent dose interruption. Poziotinib dose below 16 mg or a new scheduled dose (e.g. BID) with a high rate of tolerance.